Revolution of innovation management. Volume 1, - Brem, Alexander; Viardot, Eric (Palgrave Macmillan, 2017)
This edited collection explores how digitalization is changing the management of innovation, and the subsequent implications for the next phases in its development. The authors identify and examine relevant phenomena which are related to the ongoing digital breakthrough in the context of innovation management such as user innovation, crowd sourcing and crowd funding, as well as social media. In line with the constant globalization of innovation, the first volume of Revolution of Innovation Management offers a variety of international perspectives on these topics with illustrations and analysis coming from Asia, America, and Europe.- Resumé vydavatel
Keywords: inovace; management inovací; organizační změna; podnikový management; innovations; innovation management; organizational change; industrial management; elektronické knihy; sborníky; electronic books; papers of several authors